Panoramic radiograph measurement of upper mandibular ramus breadth for sex determination - Dinda Priscilia Septiani; Rizki Tanjung; Intan Farizka (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: This research is aimed to see the difference of the upper mandibular ramus breadth between male and female patients in Rumah Sakit Gigi dan Mulut Pendidikan (RSGMP) Fakultas Kedokteran Gigi Universitas Trisakti, West Jakarta according to radiomorphometry. Materials and Methods: This research uses observational analytical design on 166 digital panoramic radiographs, 83 male radiographs and 83 female radiographs, of patients aged 18 and above from the Installation of Dental Radiology in RSGM-P FKG Universitas Trisakti. The measurement was performed on left upper mandibular ramus breadth using the computer software i-Dixel version 2.2.0.3 (Morita Japan). The data is analyzed using comparative independent t-tests to see the difference between the genders. Results: The result of this study shows the mean value of the left upper mandibular ramus breadth in male (31.55 Â± 2.66 mm ) is higher than female (29.42 Â± 2.58 mm) with p-value = 0.000. Conclusion: The upper mandibular ramus breadth measurement shows significant difference between genders.